2020
DOI: 10.1016/j.heliyon.2020.e05196
|View full text |Cite
|
Sign up to set email alerts
|

Quality and microstructure of freeze-dried yoghurt fortified with additives as protective agents

Abstract: The effect of freeze drying of yoghurt and addition of some additives on the physico-chemical, microbiological, texture, microstructure, and sensory quality of yoghurt was studied. Freeze drying of yoghurt had light effects on the viability of Streptococcus thermophilus and no effect on viability of Lactobacillus delbreuckii subsp. bulgaricus and rehydrated yoghurt. Addition of modified starch had a considerable protection effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 20 publications
0
8
0
2
Order By: Relevance
“…However, Caparino et al [ 25 ] reported that the freeze-dried mango powder appeared as smooth flakes. Ismail et al [ 26 ] prepared freeze-dried yogurt with the addition of some additives (spirulina powder, modified starch, and whey protein concentrate). After completing freeze-drying, the resultant product had a flake-like structure.…”
Section: Resultsmentioning
confidence: 99%
“…However, Caparino et al [ 25 ] reported that the freeze-dried mango powder appeared as smooth flakes. Ismail et al [ 26 ] prepared freeze-dried yogurt with the addition of some additives (spirulina powder, modified starch, and whey protein concentrate). After completing freeze-drying, the resultant product had a flake-like structure.…”
Section: Resultsmentioning
confidence: 99%
“…Tontul et al (2018) found the moisture content of freezedried yoghurt as 8.3%. Ismail et al (2020) could manufacture freeze-dried yoghurt powder with no additive having 4.25%.…”
Section: Moisture Contentmentioning
confidence: 99%
“…There are several researches on yoghurt powder production by using different drying techniques, either applying more than one or only one technique, such as spray drying, freeze drying, refractance window drying and air drying (Koç et al, 2014;Zungur-Bastıoğlu et al, 2016;Carvalho et al, 2017;Fournaise et al, 2020;Ismail et al, 2020;Monsalve-Atencio et al, 2021). Freeze drying is applied to extend the shelf life in which the quality of the reconstituted product remains unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Pati merupakan polisakarida dengan kandungan molekul amilosa dan amilopektin pada strukturnya. Ismail et al (2020) menyatakan bahwa penambahan pati termodifikasi memberikan efek perlindungan terhadap sel Streptococcus thermophilus selama freeze drying. Charles et al (2021) juga menemukan bahwa kombinasi bahan penyalut dengan pati garut pada enkapsulasi menggunakan freeze drying menunjukkan hasil stabilitas oksidasi terbaik selama penyimpanan 90 hari.…”
Section: Pendahuluanunclassified